Description of Knowledge and Attitudes of Medical Students Regarding Diphtheria Disease and Vaccination - Yosafat, Bernhard Banggas; Susanto, Aries; Fauzi, Ahmad; Yao, Ng Chor (Jurnal MedScientiae, 2023)
Diphtheria is an upper respiratory tract disease which causes symptoms like sore throat, presence of agrayish white membrane and can also be accompanied by mild to severe fever. Diphtheria is a rapidlytransmitted disease. Diphtheria is caused by the bacterium Corynebacterium diphtheriae. This study to determine the level of knowledge Diphtheria disease andvaccination. This study uses a design is approaching therespondent directly, asking for permission, explaining the ethics used in filling out the questionnaireand the purpose of the study. Notify and explain the filling procedure to the respondent, then therespondent returns the questionnaire that has been filled out to the researcher. Sampling in this studyby taking voluntary sampling by taking into account the inclusion criteria and exclusion criteria,namely students who are active in the medical faculty of Kristen Krida Wacana University and arestudents of 2016. The results of the study obtained distribution data regarding the students' knowledgeof the Faculty of Medicine, Krida Wacana University, 2016 concerning Disease and DiphtheriaVaccination that most respondents, namely 54 (50.5%) of 107 respondents had a level of knowledgethat was categorized as good. Whereas for the level of knowledge that is categorized sufficiently as many as 44 (41.1%) and as many as 9 (8.4%) respondents have a lack of knowledge while thedistribution of attitudes of the students of the Faculty of Medicine, Kristen Krida Wacana University in2016 concerning Disease and Diphtheria Vaccination, all respondents were 107 respondents (100%)have a good attitude.